The Impact of the COVID-19 Pandemic on Auditing Practices: A Qualitative Analysis - Kusuma, Bunga Wijaya (Manunggal Halim Jaya, 2024)
This study delves into the impact of the COVID-19 pandemic on auditing practices, aiming to elucidate the challenges, adaptations, and emerging trends within the auditing profession. Through a comprehensive qualitative analysis of existing literature, the research explores the transformative effects of the pandemic on audit methodologies, regulatory dynamics, and technological innovations. The study employs a thematic analysis approach to identify key themes and patterns, drawing insights from diverse perspectives and theoretical frameworks such as contingency theory and institutional theory. The research investigates the paradigm shift in auditing methodologies necessitated by the pandemic, focusing on the challenges of conducting audits in remote work environments, navigating data security concerns, and verifying digital documentation. It examines how auditors adapt their practices to remote work conditions, implement flexible audit approaches, and leverage technology-driven solutions to maintain audit quality and integrity. Additionally, the study explores the evolving regulatory landscape in response to the pandemic and the role of audit committees in overseeing audit quality and risk management. The findings underscore the imperative of adaptability, innovation, and resilience within the auditing profession amidst ongoing disruptions and uncertainties. Overall, this research contributes to a nuanced understanding of the multifaceted implications of the pandemic on auditing practices and provides insights for developing adaptive strategies and best practices in the post-pandemic audit landscape.